Degradable Biopolymers from Agro and Food Waste: Potentials and Challenges - M, Udayamathi; V, Bhavani Poojitha; B, Harini; S.S., Gowtham; Dinakarkumar, Yuvaraj (New Environmentally-Friendly Materials, 2023)
The synthesis of biodegradable plastics from diverse biological resources has garnered significant attention in recent years. The escalating demand for petroleum-based plastics in daily life presents a growing concern due to their non-degradability and production involving hazardous chemicals. The disposal of solid waste is a pressing issue, particularly in densely populated countries like India. Biodegradable waste generated from various sectors, including agriculture, industries, and households, significantly contributes to environmental challenges. Effectively managing such waste remains a formidable challenge. Given the profound environmental impact, there is an imperative need to prioritize waste management across various sectors. Notably, biologically treated waste streams have been found to contain a rich reservoir of organic materials, which can serve as valuable feedstock for the synthesis of biodegradable plastics. Biodegradable plastics, derived from renewable biomass sources, offer an eco-friendly alternative to conventional plastics. The synthesis of biodegradable plastics from a variety of biomaterials represents the present and future frontier in mitigating environmental threats posed by commercial plastics and the accumulation of waste in landfills. This review offers comprehensive insights into the significance of bio-based plastics derived from a range of biological waste resources and their multifaceted applications across diverse fields, emphasizing their pivotal role in achieving a more sustainable and environmentally responsible future.